La actividad física - recreativa y su incidencia en el estilo de vida saludable, de los transportistas de la cooperativa “Vilcabamba Express” de la parroquia de Vilcabamba. 2013. Propuesta alternativa - Rojas Mejía, Omar Genaro (2016)
The investigation relates to physical activity - recreational that is conceptualized as the common practice is one of the elements that can contribute to healthy and pleasant to the improvement of health is also a better quality of life and lifestyle is a set of behaviors or attitudes that the individuals, who are sometimes healthy and sometimes they are harmful to health, the theme: Physical Activity and its Effect on healthy Lifestyle, operators of the Cooperative "Vilcabamba Express "of the parish of Vilcabamba, in 2013, which has the overall objective to determine whether the physical activity program - Recreational improves the Healthy Lifestyle in Carriers Cooperative" Vilcabamba Express "whose problems Central refers to: physical activity - recreation, improve Healthy Lifestyle, operators of "Vilcabamba Express" Cooperative Parish Vilcabamba ?, in the literature review categories recreational physical activity and detailed style Lifestyle, definitions, general and benefits; Synthetic, heuristic, statistical method and the inductive method - - Deductive for compliance the scientific method, the Analytical were used. The instruments applied were: survey and physical test applied to the 37 carriers of the research institution. Among the outcomes of the discussion it was decided that physical activity if you are focusing on the lifestyle of carriers, as well as planning activities completed was an alternative to improve the lifestyle of carriers, similarly, the diagnosed diseases due to lack of physical activity of the carrier of the company investigated. Among the notable findings we are: it is of poor assessment of aerobic endurance and analyzed at leisure carriers are enhancing little physical activity - recreational; Recommendations relevant stands carriers to make at least 30 minutes of physical activity - recreation, just so that their managers are planned physical activities - recreational and constituting an alternative to improve healthy lifestyle